A cloud-based architecture for emergency management and first responders localization in smart city environments. (November 2016) - Palmieri, Francesco; Ficco, Massimo; Pardi, Silvio; Castiglione, Aniello
Highlights: Emergency management solution for smart cities based on a hybrid decentralized service oriented cloud platform. Uses mobile communication and smart sensing facilities for managing command & control activities in urban areas. Supports a first responder localization service based on a hybrid positioning approach that combines Landmark-based and Landmark-free systems and leverages cloud facilities. Such approach relies on both the strength of signals received from landmark nodes and information gathered from motion sensors. Graphical abstract: Abstract: Homeland security represents one of the most relevant application contexts for smart cities, attracting the interest of both authorities and the research community. In case of a crisis event occurring in the urban area, authorities are responsible for effectively managing response operations. A critical challenge in emergency management is the lack of real-time coordinated reaction capabilities driven by integrated decision making facilities based on the information obtained by first responders acting on the crisis site. This work aims at supporting coordinated emergency management in smart cities based on the localization of first responders during crisis events. We present a hybrid cloud architecture for managing computing and storage resources needed by command & control activities in emergency scenarios, complemented by a first responder localization service relying on a novel positioning approach which combines the strength of signals received from landmarks placed by first responders on the crisis site with information obtained from motion sensors.